Особливості розрахунку неорганізованого природного повітрообміну помешкань житлових будинків - Жуковський, С.; Жуковська, 3. (Видавництво Національного університету «Львівська політехніка», 2000)
This article presents the method of calculation of the uncontrolled natural air exchange in the rooms of civil buildings, which is based on the solution of the system of nonlinear equations taking into account the total leakiness of window and door units and air pressure losses in air channels.